Membrane electrode assembly and manufacturing method thereof, hydrogen manufacturing device, and ink manufacturing method

By adding water-repellent particles imparted by fluorine groups to the anode catalyst layer and optimizing the ionomer ratio, the problems of oxygen dischargeability and hydrogen discharge efficiency in solid polymer electrolysis are solved, and more efficient hydrogen production and conductivity management are achieved.

CN115786929BActive Publication Date: 2025-04-22SCREEN HOLDINGS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202210812167.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-09-13
Filing Date
2022-07-11
Publication Date
2025-04-22
Estimated Expiration
2042-07-11

AI Technical Summary

Technical Problem

In solid polymeric water electrolysis, the reduction of oxygen discharge properties leads to a decrease in hydrogen production efficiency, and the leakage and obstruction of water leads to a decrease in hydrogen discharge efficiency.

Method used

The elimination of oxygen and hydrogen is improved by adding fluorine-based ceramic or metal water-repellent particles to the anode catalyst layer and optimizing the EW value and proportion of the ionomer.

Benefits of technology

The dischargeability of the substance in the anode catalyst layer is improved, the reduction of conductivity is suppressed, the hydrogen production efficiency is enhanced, and the moisture management is optimized.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115786929B_ABST
    Figure CN115786929B_ABST
Patent Text Reader

Abstract

A membrane electrode assembly and a manufacturing method, a hydrogen manufacturing device, and a manufacturing method of ink. The present invention provides a technology that can improve the discharge properties of substances generated in a catalyst layer. The membrane electrode assembly of the present invention has an electrolyte membrane and an anode catalyst layer (21) formed on one surface of the electrolyte membrane. The anode catalyst layer (21) contains catalyst particles (51), an ionomer (52), and water-repellent particles (53). The water-repellent particles (53) are ceramic particles endowed with fluorine groups or metal particles endowed with fluorine groups. By adding water-repellent particles (53), the discharge properties of substances generated in the anode catalyst layer (21) can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a membrane electrode assembly, a hydrogen manufacturing device, a method for manufacturing a catalyst ink, and a method for manufacturing a membrane electrode assembly. Background Art

[0002] A technology called water electrolysis has long been known for producing hydrogen (H2) by electrolyzing water (H2O). There are several types of water electrolysis depending on the electrolyte used. One of them is solid polymer water electrolysis using an ion exchange membrane (electrolyte membrane) as an electrolyte. Solid polymer water electrolysis uses a single cell in which a catalyst layer is formed on both sides of the electrolyte membrane. When performing water electrolysis, a voltage is applied between the catalyst layer on the anode side and the catalyst layer on the cathode side, and water is supplied to the catalyst layer on the anode side. As a result, the following electrochemical reaction occurs in the catalyst layer on the anode side and the catalyst layer on the cathode side. As a result, hydrogen is discharged from the catalyst layer on the cathode side.

[0003] (Anode side) 2H2O→4H + +O2+4e-

[0004] (Cathode side) 2H + +2e - →H2

[0005] Conventional solid polymer water electrolysis is described in Patent Document 1, for example.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent document 1: Japanese Patent Application Publication No. 2019-083085.

[0009] As described above, in solid polymer water electrolysis, oxygen is discharged from the catalyst layer on the anode side. Therefore, in the catalyst layer on the anode side, it is necessary to supply water and discharge oxygen. At this time, there is a situation where the discharge of oxygen is hindered due to the influence of water supplied to the catalyst layer. In this case, there is a problem that the production efficiency of hydrogen based on solid polymer water electrolysis is reduced due to the reduction in the discharge of oxygen.

[0010] In addition, in solid polymer water electrolysis, part of the water filling the catalyst layer on the anode side leaks through the electrolyte membrane to the catalyst layer on the cathode side. In addition, there is a case where the water infiltrating the catalyst layer on the cathode side hinders the discharge of the generated hydrogen. As a result, there is a problem of reduced hydrogen discharge efficiency. Summary of the invention

[0011] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a technology capable of improving the discharge performance of substances generated in a catalyst layer.

[0012] In order to solve the above-mentioned problems, the first invention of the present application is a membrane electrode assembly, which has an electrolyte membrane and an anode catalyst layer formed on one surface of the electrolyte membrane; the anode catalyst layer contains catalyst particles, ionomers and water-repellent particles; the water-repellent particles are ceramic particles endowed with fluorine groups or metal particles endowed with fluorine groups.

[0013] A second invention of the present application is the membrane electrode assembly according to the first invention, wherein the ratio of the water-repellent particles to the catalyst particles is 2 wt % or more and 20 wt % or less.

[0014] A third invention of the present application is the membrane electrode assembly according to the second invention, wherein the ratio of the water-repellent particles to the catalyst particles is 5 wt % or more and 15 wt % or less.

[0015] A fourth invention of the present application is the membrane electrode assembly according to any one of the first to third inventions, wherein the EW value of the ionomer is 950 or less.

[0016] A fifth invention of the present application is the membrane electrode assembly according to any one of the first to fourth inventions, wherein the ratio of the ionomer to the catalyst particles is 8 wt % or more and 45 wt % or less.

[0017] A sixth invention of the present application is the membrane electrode assembly according to any one of the first to fifth inventions, wherein the membrane electrode assembly is used for solid polymer water electrolysis.

[0018] A seventh invention of the present application is a hydrogen production device for producing hydrogen by solid polymer water electrolysis, comprising the membrane electrode assembly of the sixth invention.

[0019] The eighth invention of the present application is a method for manufacturing a catalyst ink that becomes an anode catalyst layer of a membrane electrode assembly, which includes: a first step of preparing a first preparation solution by mixing catalyst particles and water; a second step of preparing a second preparation solution by adding an alcohol solvent to the first preparation solution; a third step of preparing a third preparation solution by adding water-repellent particles to the second preparation solution; and a fourth step of preparing a fourth preparation solution by adding an ionomer solution to the third preparation solution, wherein the water-repellent particles are ceramic particles endowed with a fluorine group or metal particles endowed with a fluorine group.

[0020] A ninth invention of the present application is the method for producing the catalyst ink according to the eighth invention, wherein the ratio of the alcohol solvent to the catalyst ink is 15 wt % or more.

[0021] The tenth invention of the present application is a method for manufacturing a membrane electrode assembly, which includes the steps of applying the catalyst ink manufactured by the manufacturing method of the eighth invention or the ninth invention to one surface of the electrolyte membrane and drying the catalyst ink to form the anode catalyst layer.

[0022] According to the first to seventh aspects of the present application, by adding water-repellent particles to the anode catalyst layer, it is possible to improve the discharge properties of substances generated in the anode catalyst layer.

[0023] In particular, according to the second invention of the present application, it is possible to improve the discharge properties of substances generated in the anode catalyst layer and suppress a decrease in the electrical conductivity of the anode catalyst layer due to the influence of fluorine groups.

[0024] In particular, according to the third invention of the present application, it is possible to further improve the discharge properties of substances generated in the anode catalyst layer and further suppress the decrease in the electrical conductivity of the anode catalyst layer due to the influence of fluorine groups.

[0025] In particular, according to the fourth invention of the present application, the number of ion exchange groups in the polymer chain of the ionomer increases, thereby enabling the oxonium ions to be propagated well.

[0026] In particular, according to the fifth invention of the present application, the generated substances can be discharged well by covering the catalyst particles with the ionomer well and leaving gaps in the anode catalyst layer.

[0027] In particular, according to the sixth invention of the present application, by improving the discharge performance of oxygen generated in the anode catalyst layer, the hydrogen production efficiency of solid polymer water electrolysis can be improved.

[0028] In addition, according to the eighth to tenth inventions of the present application, water-repellent particles are added to the catalyst ink that becomes the anode catalyst layer. Thus, the discharge of substances generated in the anode catalyst layer can be improved. In addition, the water-repellent particles are added after the alcohol solvent is added. Thus, the water-repellent particles can be uniformly dispersed.

[0029] In particular, according to the ninth invention of the present application, the water-repellent particles can be dispersed more uniformly. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a schematic diagram of a hydrogen production device.

[0031] Figure 2 It is a schematic diagram schematically showing the composition of the anode catalyst layer.

[0032] Figure 3 is a schematic diagram of water-repellent particles.

[0033] Figure 4This is a graph showing the relationship between the amount of water-repellent particles added to the anode catalyst layer and the voltage characteristics of the hydrogen manufacturing apparatus.

[0034] Figure 5 This is a flow chart showing the procedure for producing the catalyst ink.

[0035] Figure 6 This is a flow chart showing the manufacturing procedure of the membrane electrode assembly.

[0036] Description of Reference Numerals

[0037] 1 Hydrogen production equipment

[0038] 10 Electrolyte membrane

[0039] 21 Anode catalyst layer

[0040] 22 Anode gas diffusion layer

[0041] 23 Anode seal

[0042] 24 Anode diaphragm

[0043] 31 Cathode catalyst layer

[0044] 32 Cathode gas diffusion layer

[0045] 33 Cathode sealing gasket

[0046] 34 Cathode diaphragm

[0047] 40 Power Supply

[0048] 50 membrane electrode assembly

[0049] 51 Catalyst particles

[0050] 52 Ionomer

[0051] 53 Water repellent particles

[0052] 241 Anode diaphragm groove

[0053] 341 Cathode diaphragm groove

[0054] 531 Main particles DETAILED DESCRIPTION

[0055] Hereinafter, embodiments of the present invention will be described with reference to the drawings.

[0056] <1. Configuration of hydrogen production equipment>

[0057] Figure 1 Schematic diagram of a hydrogen manufacturing device 1 according to an embodiment of the present invention. The hydrogen manufacturing device 1 is a device for manufacturing hydrogen by solid polymer water electrolysis. Figure 1As shown, the hydrogen manufacturing device 1 has a single cell, and the single cell includes an electrolyte membrane 10, an anode catalyst layer 21, an anode gas diffusion layer 22, an anode gasket 23, an anode diaphragm 24, a cathode catalyst layer 31, a cathode gas diffusion layer 32, a cathode gasket 33 and a cathode diaphragm 34. The stacked body composed of the electrolyte membrane 10, the anode catalyst layer 21 and the cathode catalyst layer 31 in each layer of the single cell is a membrane electrode assembly (MEA: Membrane-Electrode-Assembly) 50 of one embodiment of the present invention.

[0058] The electrolyte membrane 10 is a thin plate-shaped membrane (ion exchange membrane) having ion conductivity. A fluorine-based or hydrocarbon-based polymer electrolyte membrane is used as the electrolyte membrane 10. Specifically, a polymer electrolyte membrane containing perfluorocarbon sulfonic acid is used as the electrolyte membrane 10. The membrane thickness of the electrolyte membrane 10 is, for example, 5 μm to 30 μm.

[0059] The anode catalyst layer 21 is a layer that becomes an electrode on the anode side. The anode catalyst layer 21 is formed on the surface of the anode side of the electrolyte membrane 10. The anode catalyst layer 21 contains a large number of catalyst particles. The catalyst particles are, for example, iridium oxide (IrOx), platinum (Pt), an alloy of iridium (Ir) and ruthenium (Ru), an alloy of iridium (Ir) and titanium dioxide (TiO2), etc. When the hydrogen manufacturing device 1 is used, water (H2O) is supplied to the anode catalyst layer 21. In addition, a voltage is applied between the anode catalyst layer 21 and the cathode catalyst layer 31 by the power supply 40 described later. In this way, through the action of the voltage and the catalyst particles, water is electrolyzed into hydrogen ions (H + ), oxygen (O2) and electrons (e - ).

[0060] It should be noted that the more detailed composition of the anode catalyst layer 21 will be described later.

[0061] The anode gas diffusion layer 22 is a layer for uniformly supplying water to the anode catalyst layer 21 and transporting oxygen and electrons generated in the anode catalyst layer 21 to the anode separator 24. The anode gas diffusion layer 22 is stacked on the outer surface of the anode catalyst layer 21. The anode catalyst layer 21 is sandwiched between the electrolyte membrane 10 and the anode gas diffusion layer 22. The anode gas diffusion layer 22 is formed of a conductive and porous material. For example, carbon paper is used for the anode gas diffusion layer 22.

[0062] The anode gasket 23 is a layer for preventing water and oxygen from leaking from the anode catalyst layer 21 and the anode gas diffusion layer 22 to the surroundings. Figure 1 As shown, the anode gasket 23 is formed on the surface of the electrolyte membrane 10 on the anode side, and surrounds the anode catalyst layer 21 and the anode gas diffusion layer 22 .

[0063] The anode diaphragm 24 is a layer for supplying water to the anode gas diffusion layer 22 and transporting electrons flowing from the anode catalyst layer 21 through the anode gas diffusion layer 22 to the power source 40. In addition, the anode diaphragm 24 also plays a role in discharging oxygen generated in the anode catalyst layer 21 to the outside. The anode diaphragm 24 is formed on the outer surface of the anode gas diffusion layer 22 and the anode gasket 23. The anode catalyst layer 21, the anode gas diffusion layer 22 and the anode gasket 23 are sandwiched between the electrolyte membrane 10 and the anode diaphragm 24.

[0064] The anode diaphragm 24 is formed of a conductive and airtight material. In addition, a large number of grooves 241 are formed in the anode diaphragm 24. Water is supplied to the anode gas diffusion layer 22 through the grooves 241 of the anode diaphragm 24. In addition, oxygen generated in the anode catalyst layer 21 passes through the anode gas diffusion layer 22 and is discharged to the outside through the grooves 241 of the anode diaphragm 24.

[0065] The cathode catalyst layer 31 is a layer that becomes an electrode on the cathode side. The cathode catalyst layer 31 is formed on the cathode side surface of the electrolyte membrane 10 (the surface on the opposite side to the anode catalyst layer 21). The cathode catalyst layer 31 includes a large number of carbon particles carrying catalyst particles. The catalyst particles are, for example, platinum particles. However, the catalyst particles may also be particles formed by mixing a small amount of ruthenium or cobalt particles in platinum particles. When the hydrogen manufacturing device 1 is used, hydrogen ions (H 2+) are supplied to the cathode catalyst layer 31. + ) and electron (e - ). Then, a voltage is applied between the anode catalyst layer 21 and the cathode catalyst layer 31 by a power supply 40 described later. Thus, a reduction reaction occurs in the cathode catalyst layer 31 by the action of the voltage and the catalyst particles, and hydrogen (H2) is generated from hydrogen ions and electrons.

[0066] The cathode gas diffusion layer 32 is a layer for transporting electrons from the cathode separator 34 to the cathode catalyst layer 31 and transporting hydrogen generated in the cathode catalyst layer 31 to the cathode separator 34. The cathode gas diffusion layer 32 is stacked on the outer surface of the cathode catalyst layer 31. The cathode catalyst layer 31 is sandwiched between the electrolyte membrane 10 and the cathode gas diffusion layer 32. The cathode gas diffusion layer 32 is formed of a conductive and porous material. For example, carbon paper is used for the cathode gas diffusion layer 32.

[0067] The cathode gasket 33 is a layer for preventing hydrogen from leaking from the cathode catalyst layer 31 and the cathode gas diffusion layer 32 to the surroundings. Figure 1 As shown, the cathode gasket 33 is formed on the surface of the electrolyte membrane 10 on the cathode side, and surrounds the cathode catalyst layer 31 and the cathode gas diffusion layer 32 .

[0068] The cathode diaphragm 34 is a layer for transporting electrons supplied from the power source 40 to the cathode gas diffusion layer 32 and discharging the generated hydrogen to the outside. The cathode diaphragm 34 is formed on the surface of the outer side of the cathode gas diffusion layer 32 and the cathode gasket 33. The cathode catalyst layer 31, the cathode gas diffusion layer 32 and the cathode gasket 33 are sandwiched between the electrolyte membrane 10 and the cathode diaphragm 34. The cathode diaphragm 34 is formed of a conductive and airtight material. In addition, a large number of grooves 341 are formed on the cathode diaphragm 34. Hydrogen is discharged from the cathode gas diffusion layer 32 to the outside through the grooves 341.

[0069] The power source 40 is connected between the anode separator 24 and the cathode separator 34. Specifically, the positive terminal of the power source 40 is electrically connected to the anode separator 24. The negative terminal of the power source 40 is electrically connected to the cathode separator 34. The power source 40 applies a voltage required for electrolysis of water between the anode separator 24 and the cathode separator 34.

[0070] When the hydrogen manufacturing device 1 is used, water is supplied from the anode diaphragm 24 to the anode catalyst layer 21 via the anode gas diffusion layer 22. In this way, water is decomposed into hydrogen ions, oxygen and electrons by the action of the voltage of the power supply 40 and the catalyst particles of the anode catalyst layer 21. The hydrogen ions propagate to the cathode catalyst layer 31 through the electrolyte membrane 10. Oxygen is discharged to the outside through the anode gas diffusion layer 22 and the anode diaphragm 24. Electrons flow to the cathode catalyst layer 31 through the anode gas diffusion layer 22, the anode diaphragm 24, the power supply 40, the cathode diaphragm 34 and the cathode gas diffusion layer 32. In addition, in the cathode catalyst layer 31, hydrogen ions are combined with electrons to generate hydrogen. The generated hydrogen is discharged to the outside through the cathode gas diffusion layer 32 and the cathode diaphragm 34. Thus, hydrogen is produced.

[0071] <2. Composition of anode catalyst layer>

[0072] Next, a more detailed composition of the anode catalyst layer 21 will be described.

[0073] Figure 2 Schematic diagram schematically showing the composition of the anode catalyst layer 21. Figure 2 As shown, the anode catalyst layer 21 includes a plurality of catalyst particles 51 , an ionomer 52 , and a plurality of water-repellent particles 53 .

[0074] The catalyst particles 51 are particles for causing electrolysis of water. For example, iridium oxide, platinum, an alloy of iridium and ruthenium, an alloy of iridium and titanium dioxide, or the like is used as the catalyst particles 51.

[0075] The ionomer 52 is an electrolyte polymer covering the catalyst particles 51. The ionomer 52 plays a role in transporting hydrogen ions generated by electrolysis of water in the anode catalyst layer 21. For example, Nafion (perfluorocarbon sulfonic acid) is used for the ionomer 52. The ionomer 52 has a polymer chain structure having an ion exchange group such as a sulfonic group. The hydrogen ions combine with the water in the cathode catalyst layer 31 to form oxonium ions (H3O + ). In addition, the oxonium ions propagate through the ion exchange groups of the ionomer 52.

[0076] In order to propagate the oxonium ions well, it is preferable to increase the number of ion exchange groups in the polymer chain of the ionomer 52. Specifically, the EW value representing the dry mass of the ionomer 52 per 1 mol of the ion exchange group (the inverse of the number of ion exchange groups per unit mass of the ionomer 52) is preferably 950 or less. For example, the EW value can be set to 650 or more and 950 or less.

[0077] When the ratio of the ionomer 52 to the catalyst particles 51 is too small, the catalyst particles 51 cannot be sufficiently covered with the ionomer 52. As a result, it becomes difficult to propagate the oxonium ions well through the ionomer 52. On the other hand, when the ratio of the ionomer 52 to the catalyst particles 51 is too large, the voids in the cathode catalyst layer 31 are reduced. As a result, the diffusion of water in the anode catalyst layer 21 and the discharge of oxygen generated in the anode catalyst layer 21 are hindered.

[0078] Therefore, it is preferred that the ratio of the ionomer 52 to the catalyst particles 51 is such that the catalyst particles 51 can be well covered with the ionomer 52 and water diffusion and oxygen discharge can be well performed. Specifically, it is preferred that the ratio (weight ratio) of the ionomer 52 to the catalyst particles 51 is 8 wt% or more and 45 wt% or less. It is more preferred that the ratio (weight ratio) of the ionomer 52 to the catalyst particles 51 is 10 wt% or more and 25 wt% or less.

[0079] The water-repellent particles 53 are additives for improving the oxygen discharge performance in the anode catalyst layer 21 . Figure 3 Schematic diagram of water-repellent particles 53. Figure 3 As shown, the water-repellent particles 53 are formed by imparting a plurality of water-repellent fluorine-based (F) particles on the surface of the main particles 531. The main particles 531 are, for example, ceramic particles or metal particles. The ceramic particles are, for example, titanium oxide (TiO2) particles. The metal particles are, for example, precious metal particles such as platinum (Pt), silver (Ag), and gold (Au). The diameter of the water-repellent particles 53 is, for example, greater than 2 nm and less than 500 nm.

[0080] Water is present in the anode catalyst layer 21 and a high voltage of about 2 V is applied. Therefore, if carbon particles are used as the main particles 531, oxidation of carbon (electron emission) is carried out in parallel with electrolysis. Specifically, the following chemical reaction occurs, resulting in the disappearance of carbon (C). Therefore, instead of using carbon particles as the main particles 531, ceramic particles or metal particles are preferably used as described above.

[0081] C + H2O → CO + 2H + +2e-

[0082] Figure 4 Graph showing the relationship between the amount of water-repellent particles 53 added to the anode catalyst layer 21 and the voltage characteristics of the hydrogen manufacturing apparatus 1. Figure 4 In the graph of , the horizontal axis represents the ratio (weight ratio) of the water-repellent particles 53 to the catalyst particles 51. The vertical axis represents the voltage value to be applied from the power source 40 in order to generate a predetermined amount of hydrogen. Figure 4 The graph shows that the current density is 2.0 A / cm 2 The voltage value at that time.

[0083] When the water-repellent particles 53 are added to the anode catalyst layer 21, the water in the anode catalyst layer 21 is repelled by the water-repellent effect of the fluorine group. As a result, the movement of oxygen generated in the anode catalyst layer 21 becomes less likely to be hindered by water. Therefore, oxygen can be efficiently discharged from the anode catalyst layer 21. In addition, when the discharge of oxygen is improved, the electrolysis of water in the anode catalyst layer 21 is further promoted.

[0084] In addition, when the water-repellent particles 53 are added to the anode catalyst layer 21, water in the anode catalyst layer 21 is prevented from penetrating into the cathode catalyst layer 31 through the electrolyte membrane 10. Therefore, the movement of hydrogen generated in the cathode catalyst layer 31 becomes less likely to be hindered by water. Therefore, hydrogen can be efficiently discharged from the cathode catalyst layer 31.

[0085] Through these effects, such as Figure 4 As shown, when the water-repellent particles 53 are added to the anode catalyst layer 21, the voltage value to be applied from the power source 40 can be reduced compared to the case where the water-repellent particles 53 are not added. That is, the efficiency of producing hydrogen by solid polymer water electrolysis can be improved.

[0086] However, when the amount of water-repellent particles 53 added is too large, the resistance of the anode catalyst layer 21 increases due to the influence of the insulating fluorine groups. Figure 4 In the case where the weight ratio of the water-repellent particles 53 to the catalyst particles 51 is 25 wt %, the voltage value to be applied from the power source 40 increases instead.

[0087] Therefore, the amount of water-repellent particles 53 added is preferably an amount that can improve the discharge of oxygen generated in the anode catalyst layer 21 and can suppress the decrease in the conductivity of the anode catalyst layer 21 due to the influence of the fluorine group. Specifically, the ratio (weight ratio) of the water-repellent particles 53 to the catalyst particles 51 is preferably greater than 2wt% and less than 20wt%. In addition, it is more preferred that the ratio (weight ratio) of the water-repellent particles 53 to the catalyst particles 51 is greater than 5wt% and less than 15wt%. For example, the ratio (weight ratio) of the water-repellent particles 53 to the catalyst particles 51 can be 10wt%.

[0088] As described above, in the anode catalyst layer 21, hydrogen ions are propagated in the form of oxonium ions by combining with water. Therefore, in order to improve the propagation efficiency of hydrogen ions, it is preferable to uniformly maintain a certain degree of moisture in the anode catalyst layer 21. However, when the moisture is too much, the discharge of oxygen in the anode catalyst layer 21 is hindered. Therefore, in the anode catalyst layer 21, it is preferable to optimize the amount of moisture retained.

[0089] In this regard, reducing the EW value of the ionomer 52 will work in the direction of increasing the water content in the anode catalyst layer 21. On the other hand, adding the water-repellent particles 53 will work in the direction of reducing the water content in the anode catalyst layer 21. Therefore, as described above, by making the EW value of the ionomer 52 less than 950 and adding the water-repellent particles 53, the amount of water retained in the anode catalyst layer 21 can be maintained within an appropriate range. As a result, the production efficiency of hydrogen based on solid polymer water electrolysis can be further improved.

[0090] <3. Catalyst ink production process>

[0091] The anode catalyst layer 21 is formed by applying a catalyst ink in a paste form onto the surface of the electrolyte membrane 10. Hereinafter, a method for producing the catalyst ink that becomes the anode catalyst layer 21 will be described.

[0092] Figure 5 is a flow chart showing the manufacturing process of the catalyst ink. Figure 5 As shown, when preparing the catalyst ink, first, the catalyst particles 51 and water are mixed to prepare a first mixed solution (first step S1). In the first step S1, water is added to prevent the catalyst particles 51 from igniting.

[0093] Next, an alcohol solvent is added to the first prepared solution to prepare a second prepared solution (second step S2). The alcohol solvent is, for example, methanol, ethanol, 1-propanol, or 2-propanol.

[0094] Next, a third mixed solution is prepared by adding water-repellent particles 53 to the second mixed solution (third step S3). The water-repellent particles 53 are ceramic particles endowed with fluorine groups or metal particles endowed with fluorine groups. In the third step S3, the water-repellent particles 53 are dispersed in the alcohol solvent added in the second step S2.

[0095] If the water-repellent particles 53 are added in the first step S1, the water-repellent particles 53 are not dispersed in the first prepared solution and tend to form agglomerates due to the water-repellent effect of the fluorine group. In contrast, in the present embodiment, in the second step S2, an alcohol solution with a small contact angle (high affinity for the water-repellent particles 53) is added in advance, and then the water-repellent particles 53 are added in the third step S3. Thus, the water-repellent particles 53 can be uniformly dispersed in the third prepared solution.

[0096] Then, the fourth mixed solution is prepared by adding the ionomer solution to the third mixed solution (fourth step S4). The ionomer solution is a solution formed by dissolving the ionomer 52 in water and alcohol. Since the water ratio in the ionomer solution is high, the water-repellent particles 53 are added and dispersed in the third step S3.

[0097] Thereafter, the fourth blending liquid is further subjected to a dispersion treatment (fifth step S5). In the fifth step S5, for example, the fourth blending liquid is stirred. Thus, the water-repellent particles 53 are more uniformly dispersed in the fourth blending liquid. As a result, a catalyst ink is generated. It should be noted that the ratio (weight ratio) of the alcohol solvent to the catalyst ink finally generated is preferably 15wt% or more. Thus, the dispersibility of the water-repellent particles 53 in the catalyst ink can be further improved.

[0098] <4. Method for manufacturing membrane electrode assembly>

[0099] Next, a method for producing the membrane electrode assembly 50 using the above-mentioned catalyst ink will be described.

[0100] Figure 6 FIG. 5 is a flow chart showing the manufacturing procedure of the membrane electrode assembly 50. Figure 6 As shown, when manufacturing the membrane electrode assembly 50, the catalyst ink for the anode manufactured by the above-mentioned procedure is applied to one surface of the electrolyte membrane 10 (sixth step S6). Then, the applied catalyst ink is dried (seventh step S7). Thus, the anode catalyst layer 21 is formed on one surface of the electrolyte membrane 10.

[0101] In addition, a catalyst ink for the cathode is applied to the other surface of the electrolyte membrane 10 (eighth step S8). In addition, the applied catalyst ink is dried (ninth step S9). Thus, the cathode catalyst layer 31 is formed on the other surface of the electrolyte membrane 10. As a result, a membrane electrode assembly 50 consisting of the electrolyte membrane 10, the anode catalyst layer 21 and the cathode catalyst layer 31 is obtained.

[0102] It should be noted that the sixth step S6 and the seventh step S7 for forming the anode catalyst layer 21 and the eighth step S8 and the ninth step S9 for forming the cathode catalyst layer 31 may be performed in reverse order.

Claims

1. A membrane electrode assembly for solid polymer water electrolysis, wherein: have: Electrolyte membrane; as well as an anode catalyst layer formed on one surface of the electrolyte membrane, The anode catalyst layer comprises: Catalyst particles; ionomers; and Water repellent particles, The water-repellent particles are ceramic particles endowed with fluorine groups. The ratio of the water-repellent particles to the catalyst particles is 2 wt % or more and 20 wt % or less.

2. The membrane electrode assembly according to claim 1, wherein: The ratio of the water-repellent particles to the catalyst particles is 5 wt % or more and 15 wt % or less.

3. The membrane electrode assembly according to claim 1 or 2, wherein: The EW value of the ionomer is 950 or less.

4. The membrane electrode assembly according to claim 1 or 2, wherein: The ratio of the ionomer to the catalyst particles is 8 wt % or more and 45 wt % or less.

5. A hydrogen production device for producing hydrogen by solid polymer water electrolysis, wherein: A membrane electrode assembly according to any one of claims 1 to 4 is provided.

6. A method for producing a catalyst ink which is a catalyst ink for forming an anode catalyst layer of a membrane electrode assembly for solid polymer water electrolysis, wherein: Include: In the first step, the catalyst particles and water are mixed to prepare a first mixed solution; The second step is to prepare a second prepared solution by adding an alcohol solvent to the first prepared solution; A third step is to prepare a third prepared solution by adding water-repellent particles to the second prepared solution; as well as The fourth step is to prepare a fourth mixed solution by adding the ionomer solution to the third mixed solution. The water-repellent particles are ceramic particles endowed with fluorine groups. The ratio of the water-repellent particles to the catalyst particles is 2 wt % or more and 20 wt % or less.

7. The method for producing a catalyst ink according to claim 6, wherein: The ratio of the alcohol solvent to the catalyst ink is 15 wt % or more.

8. A method for manufacturing a membrane electrode assembly, wherein: The method comprises the steps of applying the catalyst ink produced by the production method according to claim 6 or 7 to one surface of an electrolyte membrane and drying the catalyst ink to form the anode catalyst layer.

Citation Information

Patent Citations

  • Paste for forming electrode catalyst layer, manufacturing method, film-electrode catalyst layer conjugant, gas diffusion electrode, solid polymer fuel cell, and manufacturing method of solid polymer water electrolysis cell

    JP2019083085A

  • Membrane electrode assembly and manufacturing method thereof, battery, and catalyst ink manufacturing method

    CN115799526A

  • Membrane electrode assembly, polymer electrolyte fuel cell, method of producing catalyst ink, and method of producing membrane electrode assembly

    EP4148842A1

  • Membrane electrode assembly, hydrogen producing device, method of producing catalyst ink, and method of producing membrane electrode assembly

    EP4177380A2

  • Fuel cell and membrane electrode assembly

    US20050214631A1